ANTIOXIDANT ACTIVITY OF POMEGRANATE RIND EXTRACTS (Punica granatum L.) FROM DIFFERENT EXTRACTION METHOD - Tantriska Wijanti; Eva Pahlani; Rizky Kartika Lestari (LPPM Universitas Bakti Tunas Husada, 2023)
Pomegranate (Punica granatum L.) is a fruit that has many properties and benefits, including the rind. However, so far people have only consumed the seeds and discarded the rind. Pomegranate peel is efficacious as an antioxidant that can counteract free radicals. This study aims to compare the antioxidant activity of pomegranate peel extract from two different extraction methods with the DPPH (1,1-diphenyl-2-pikrilhidrazyl) method. Pomegranate rind simplicia was extracted by hot method using the soxhlet method and cold method by maceration method. The solvent used is 70% ethanol. The extract obtained was then concentrated with a rotary vacuum evaporator and compared to its profile. From the maceration method, extracts were obtained with a yield of 33.4615%; water content 13.79%; and specific gravity of 0.8591 g/mL (5%). Meanwhile, from the sokhlet method, extracts were obtained with a yield of 32.8087%; water content of 13.50% and specific gravity of 0.8574 g/mL (5%). Examination by thin layer chromatography showed that both extracts contained gallic acid as the identity compound. The results of the phytochemical screening showed that both extracts contained alkaloids, monoterpenoids/sesquiterpenoids, flavonoids, tannins, and quinones. Meanwhile, saponin group compounds are only contained in macerated extracts. Antioxidant activity testing was carried out using the UV-Vis spectrophotometry method. The test results showed that the IC50 values of macerated and sokhlet extracts were 12.51 and 10.91 ppm, respectively. These results indicate that both extracts are classified as very strong antioxidants.